The Government's Role in Legal Protection of Bankrupt Creditors - Timotius Tumbur Simbolon; Wiwik Sri Widiarty (Universitas Dharma Wacana, 2022)
The government has issued several Laws and Regulations - Invitations to overcome the economic impact of Covid-19 due to the increasing number of bankruptcies and Suspension of Debt Payment Obligations (DPO-PKPU) in court. Therefore, the government issued a policy through Financial Services Authority (FSA-OJK) Regulation Number 48/POJK.03/2020 of 2020 concerning Amendments to FSA Regulation Number 11/POJK.3/2020 concerning National Economic Stimulus as a Countercyclical Policy Impact of the Spread of Corona Virus Disease 2019. However, previously the government had issued Law Number 37 of 2004 concerning Bankruptcy and PKPU as a form of legal protection for Bankruptcy, especially recently since Indonesia experienced the Covid-19 pandemic. In general, the economy has not been comprehensively resolved, so creditors and debtors, in solving their problems, prefer to carry out legal settlements through Bankruptcy and PKPU. In this study, there are several problems, namely, 1) What is the role of the government towards creditors under the Law on Bankruptcy and PKPU; 2) What forms of legal protection arrangements are provided for Bankruptcy? This research method uses normative or doctrinal juridical research, namely legal research that is based on or refers to the application of legal norms or norms contained in the Legislation - Invitation concerning the role of government in legal protection of Bankruptcy based on the Bankruptcy Act and PKPU.